2021
DOI: 10.1007/s00270-020-02742-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Emprint and Amica Microwave Ablation Systems in ex vivo Porcine Livers: Sphericity and Reproducibility Versus Size

Abstract: Purpose To investigate the performance of two microwave ablation (MWA) systems regarding ablation volume, ablation shape and variability. Materials and Methods In this ex vivo study, the Emprint and Amica MWA systems were used to ablate porcine livers at 4 different settings of time and power (3 and 5 minutes at 60 and 80 Watt). In total, 48 ablations were analysed for ablation size and shape using Vitrea Advanced Visualization software after acquisition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The sphericity index of the EMPRINT antenna, calculated from the LAD and SAD, demonstrated high values with an average of 0.87 and 0.92 for ex vivo and in vivo, respectively. These values are consistent with the findings from other studies on the EMPRINT antenna [ 32 , 33 ]. However, the in vivo sphericity index calculated in this study was approximately 5.4% higher than the ex vivo-derived value.…”
Section: Discussionsupporting
confidence: 93%
“…The sphericity index of the EMPRINT antenna, calculated from the LAD and SAD, demonstrated high values with an average of 0.87 and 0.92 for ex vivo and in vivo, respectively. These values are consistent with the findings from other studies on the EMPRINT antenna [ 32 , 33 ]. However, the in vivo sphericity index calculated in this study was approximately 5.4% higher than the ex vivo-derived value.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is commensurate with previous ex vivo as well as clinical studies. Hendriks et al reported a similar SI of 0.89 when using the Emprint system using various power (60 W and 80 W) and time (3 and 5 min) combinations in an ex vivo porcine liver model [ 16 ]. Hendriks et al also compared the Emprint system with the Amica system and reported significantly more spherical ablations compared with the Amica system (SI = 0.59, p < 0.01) [ 16 ].…”
Section: Discussionmentioning
confidence: 96%
“…Considering these data, the radiologist can select the probe position, energy delivered and duration of ablation. The data provided by the MWA device manufacturer are based on ex vivo and in vivo experiments and, although several case series have been published, there is no statistical analysis to date that describes the clinical utility and safety of this technology [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%